NUMBER OF VISITORS ON CROSS-DENSITY WEBSITE - Tri Indah Astuti; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2009)
The Internet is the medium of the most inexpensive, effective and fast in    convey information. Other media such as brochures for example have to do print and send activity is physically so it will require a long time in its delivery. For very large cost of television media, and only Just a few seconds can be displayed.   With the internet enough to pay for the internet, creating websites and updating the contents. Demikan Although it does not mean anything if the website are not visited by people. Effort is needed to the website can be visited by many people. The most effective way to bring visitors on the website is through Search Engine Optimization, or better known as SEO.   Search Engine Optimization is a technique that Optimizer website  created easily found or indexed by search engines such as Google. With these techniques will make the website are the results diurutan Google search that will certainly make it easier for other people can access website and automatically beneficial.   For the implementation can be tested directly on the website follow some guidelines for search engines, especially Google. With the Search Engine Optimization is expected that the site owners or a website can increase the number of visitors the website and at once introduce and increase its revenue with the website.